2021
DOI: 10.1097/j.pain.0000000000002549
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuropathic pain behaviors correlate with synaptic plasticity and limbic circuit alteration: a comparative observational study in mice

Abstract: Neuropathic pain has long-term consequences in affective and cognitive disturbances, suggesting the involvement of supraspinal mechanisms. In this study, we used the spared nerve injury (SNI) model to characterize the development of sensory and aversive components of neuropathic pain and to determine their electrophysiological impact across prefrontal cortex and limbic regions. Moreover, we evaluated the regulation of several genes involved in immune response and inflammation triggered by SNI. We showed that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Animals develop robust allodynia and pain-like behavior that last for months after the tibioperoneal nerves are cut at SNI. 16 , 20 , 59 In line with other studies, 17 , 27 , 32 , 37 , 65 we focused on early plasticity responses (7, 14 days) after nerve injury. Early responses are also observed in injury models of the central nervous system.…”
Section: Discussionmentioning
confidence: 92%
“…Animals develop robust allodynia and pain-like behavior that last for months after the tibioperoneal nerves are cut at SNI. 16 , 20 , 59 In line with other studies, 17 , 27 , 32 , 37 , 65 we focused on early plasticity responses (7, 14 days) after nerve injury. Early responses are also observed in injury models of the central nervous system.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the rate of CPSP with neuropathic component was lower than those reported in studies in young adult and pediatric patients [29,30], although direct comparisons are not possible because of difference in patient characteristics. The protective impact of aging on the occurrence of neuropathic pain has been indicated in animal experiment, and the possible mechanisms include thickness of nerve sheath, nerve injury, and weaker glial activation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and cold allodynia occurred on the 3rd and 4th days after SNI surgery, respectively, and the allodynia was maintained until the end of the experiment. Previous studies have shown that the SNI model induced mechanical and cold allodynia for 12 months [ 25 ], which is suitable for the study of the effect of long-term regular exercise on pain. Studies have shown that high-intensity exercise has a better analgesic effect than low-intensity exercise [ 26 ], but excessive high-intensity exercise may aggravate pain in mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%